A study on the different characteristics of fermented and synthetic vinegar - Bernardino, Elyn Divina N.
All fermented coconut oil and sugarcane vinegars produced on a laboratory scale were able to meet the standards (Adminidtrative Order, No. 134 s 1970) of the total acidity, total solids, total ash and lead content. The BFAD standards for vinegar do not specify limits for ammonia value and total nitrogen. Samples of commercial brands of vinegars obtained from supermarkets did not meet some of the BFAD standards than 1.5 % w/v; total acidity of the two brands of the commercial vinegars gave mean alues f less than 4% w/v; and ash contents of all commercial samples were less than 0.18%. resuls of the analyses for total solids, total ash, oxidation value, ester value and albuminoid ammonia value, showed that alues of these determinations for fermented vinegars. Likewise, values for fixed acidity in commercial and adulterated sugarcane vinegars were lower than those of fermented vinegar. As for ph, total acidity, and nitrogen content, no differences were observed among the commercial, fermented and adulterated vinegars. A comparison of the results of the analyses on sugarcane and coconut vinegars indicated that the following set of properties: fixed acidity, total solids, oxidation value, ester value and albuminoid ammonia value, could be used to distinguish conclusively feremted vinegars from adulterated vinegars.